A multidisciplinary and structured approach for comprehensive evaluation of functional outcomes, adverse events, psychosocial outcomes and health-related quality of life after local therapy for bone sarcoma in children: protocol for a cross-sectional study - Tigelaar, Leonie G.; Haveman, Lianne M.; Bekkering, Willem P.; Oude Lansink, Irene L. B.; Rohrich, Christel D.; Van der Hoek, Hinke; Beek, Laura R.; Van Dijk, Jennifer; Langemeijer, Marjolein E. M.; Slooff-Lentink, Relinde W.; Van der Aa-Van Delden, Alied M.; Maurice-Stam, Heleen; et al. (Frontiers in Pediatrics, 2025)
IntroductionBone sarcoma patients face intensive treatment, including life-changing local therapy, which impacts both short- and long-term functioning. Moreover, bone sarcoma survivors experience the highest burden of adverse events of all childhood cancer survivors. To address these issues, we set up a structured multidisciplinary outpatient follow-up clinic for patients who completed treatment and integrated this clinic into the standard of care. This study protocol describes the methodology of a cross-sectional study that aims to systematically report the functional outcomes, adverse events, psychosocial outcomes and health-related quality of life of the cohort seen at this clinic.Methods and analysisParticipants are recruited at the multidisciplinary follow-up clinic and their consent is obtained. Standard of care clinical assessments serve as the primary data source for this study. Furthermore, additional research assessments are performed to further expand our knowledge. Assessments are structured by standardized assessment sets that we developed based on literature review and joint national expertise in bone sarcoma care. The sets comply with international guidelines such as the World Health Organization's International Classification of Functioning, disability and health, and include a combination of patient-reported, clinician-reported and performance-based outcome measures for comprehensive representation of outcomes.DiscussionThis study will generate valuable knowledge on the functional outcomes, adverse events, psychosocial outcomes and quality of life of a national cohort of pediatric bone sarcoma patients in follow-up care. By aligning additional research assessments with standardized patient care, a comprehensive range of outcomes will be obtained while minimizing the patient's burden. Moreover, this protocol may serve as a template for clinics and research internationally, allowing for the merging of standardized outcome data in such rare disease. This will facilitate the optimization of current patient care and inform the important shared decision-making process for local treatment in future patients.